Risks Management and Financial Performance of Commercial Banks: A Case Study of Centenary Bank Mukono Branch - Hadijah Acelun (Uganda Christian University, 2024)
The purpose of this study was to assess the effect of risk management on financial performance of commercial banks in Uganda taking a case study of Centenary bank Mukono branch. The specific objectives of this study included: to establish the effect of credit risk on financial performance of commercial banks in Uganda; to determine the effect of liquidity risk on financial performance of commercial banks in Uganda; and, to assess the effect of operational risk on financial performance of commercial banks in Uganda. Descriptive research design was adopted in this research. Both primary and secondary data were used in this study. Data was collected from 40 staff of Centenary Bank using structured questionnaire. The staff were sampled from a population of 60 staff. The findings of this study indicated a significant association between credit risk management and financial performance of the bank. The findings also showed a significant relationship between liquidity risk and financial performance of the bank. From the findings of this study, it can be concluded that credit risk and liquidity risk could impact negatively on the financial performance and therefore, since proper management of these risks enhances financial performance, the commercial banks should put up strong structures to control these risks. This will in turn improve the financial performance of the banks. Therefore, there is need to set up strong structures for management of credit risk in order to enhance financial performance. The bank management should also give utmost priority to address the liquidity problems of the bank. This is because liquidity risk management positively influences financial performance. Therefore, the issues relating to liquidity should be promptly addressed, and immediate remedial measures taken to avoid the consequences of the bank becoming illiquid.
Undergraduate Research